Enriching Students Pays Off: Evidence from an Individualized Gifted and Talented Program in Secondary Education - Adam S. Booij; Ferry Haan; Erik Plug (Institute for the Study of Labor (IZA), 2016)
We examine the effect of a gifted and talented program in academic secondary education. Students are assigned based on a cutoff score in a cognitive aptitude test, which we exploit in a fuzzy regression discontinuity framework to identify program effects. We find that assigned students obtain higher grades, follow a more science intensive curriculum (most notably for girls), and report stronger beliefs about their academic abilities. We also find that these positive effects persist in university, where students choose more challenging fields of study with, on average, higher returns. Together, these findings are consistent with a human capital interpretation.
Keywords: I22; I28; 330; gifted and talented education; enrichment program; secondary education; regression discontinuity